A new frog species (Myobatrachidae: Uperoleia) from the Northern Deserts region of Australia, with a redescription of U. trachyderma - Catullo, Renee A.; Doughty, Paul; Keogh, J. Scott (Zootaxa, 2014)
The frog genus Uperoleia (Myobatrachidae) is species rich, with the greatest diversity in the northern monsoonal region of Australia. Due in part to their small body size, conservative morphology and distribution in diverse habitats, the genus is likely to harbor cryptic species. A recent study (Catullo et al. 2013) assessed region-wide genetic, acoustic and phenotypic variation within four species in northern Australia. Catullo et al. (2013) presented multiple lines of evidence that the widespread U. trachyderma comprises distinct allopatric western and eastern lineages within the Northern Deserts bioregion of Australia. Here we formally describe the western lineage as U. stridera sp. nov. and redescribe the eastern (type) clade as U. trachyderma. The new species can be distinguished from U. trachyderma by fewer pulses per call, a faster pulse rate, and the lack of scattered orange to red flecks on the dorsum. The description of U. stridera sp. nov. brings the number of Uperoleia species to 28, by far the largest genus in the Myobatrachidae, and further highlights the Australian monsoonal tropics as a region of high endemism.